A novel human blood-plasma separation efficiency measurement method based on ultrasonic technique - Muhammed Sabri, Salim
Clinical diagnosis of disease relies on the preliminary conclusions provided by blood testing. Accurate disease diagnosis exemplifies the crucial importance of proper separation of the blood plasma, which contains antibodies and proteins, from the platelets and red and white blood cells before testing. The most common method of clinical blood separation is via centrifugation, based on sedimentation theory. Inaccuracy of blood-plasma separation occurs not only because cells vary from one person to another in their size and density but also due to variations in the human age, cellular environment and measurement technique. In addition, the sedimentation rate is affected by changes in the viscosity and density of the sample, which can lead to incomplete separation. The separation efficiency of a laboratory centrifuge device is enhanced by combining acoustic theory with sedimentation theory. The behaviour of waves propagating through a liquid during centrifugation is studied, and the acoustic transfer function model is derived. The derived acoustic transfer function facilitates the process of system performance assessment based on an off-line test of how changes in acoustic impedance affect a solution. This assessment will help to avoid costly experimental validation studies. Low concentrations of blood cells suspended in plasma samples were detected and measured via a new ultrasound pulse technique called Power-Pulser Decay (PPD). The PPD generates multi-decay pulses that are injected into the blood sample for a discrete centrifugation process to yield the detection ability for low concentrations of particles in a liquid. As a result, a new mathematical model for the separation efficiency is derived. This model is based on experimental work and defines the separation time of a constant working spinning velocity, which results in an optimised separation time for a predefined input of the separation efficiency. Based on these results, a new centrifugation controller is designed, and its performance is simulated. The results of the centrifugation time model demonstrate that centrifugation for 3 minutes at 3000 rpm for a 0.35-ml volume is sufficient to produce plasma with separation efficiency range of (95-100)%. The volume of 0.35 ml of 1ml blood sample was selected because this volume is sufficient for multiple types of disease tests. New centrifuge controller is designed based on a Fuzzy Logic Controller. The optimisation time model reveals that this controller saves approximately 2 minutes with 95% separation efficiency compared with the PID centrifuge controller. The new centrifuge controller allows for adjustable separation accuracy, a shorter separation time and low power consumption in comparison with the commercial centrifuge device. The controller successfully saves 18kWh monthly for assuming that the centrifuge is operated 100 times per day. The improved separation efficiency will lead to broad improvements in the centrifugation process, including the ability to define the percentage of separation and the separation accuracy for the contents of a solution. In medical applications, this technique will result in more accurate test results that can be obtained more quickly, which will improve the ability of physicians and patients to make important clinical decisions.